The Effect of Stakeholder’s Pressure on Firm Performance and the Moderating Role of Perceived Economic Crisis (International Journal of Applied Research in Management and Economics, 2020)
The stakeholder pressure is one of the institutional pressures, in this regard, organizations have their internal characteristics to match the expectations of key stakeholders in the environment. In the present study, the effect of stakeholder’s pressure on firm performance was examined considering the moderating role of the perceived economic crisis. To investigate relationships, 208 questionnaires were collected from firms listed in the Tehran stock exchange. Structural equation modeling and PLS software were used to investigate the relationships. The results of this study showed that stakeholder’s pressure has a positive effect on firm performance, and perceived economic crisis reduces firm performance, and when firms believe to more likely to be in crisis, the positive effect of stakeholder’s pressure on firm performance was decreased.